2015
DOI: 10.1002/humu.22728
|View full text |Cite
|
Sign up to set email alerts
|

Two Siblings with Homozygous Pathogenic Splice-Site Variant in Mitochondrial Asparaginyl-tRNA Synthetase (NARS2)

Abstract: A homozygous missense mutation (c.822G>C) was found in the gene encoding the mitochondrial asparaginyl-tRNA synthetase (NARS2) in two siblings born to consanguineous parents. These siblings presented with different phenotypes: one had mild intellectual disability and epilepsy in childhood, whereas the other had severe myopathy. Biochemical analysis of the oxidative phosphorylation (OXPHOS) complexes in both siblings revealed a combined complex I and IV deficiency in skeletal muscle. In-gel activity staining af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 50 publications
2
52
0
Order By: Relevance
“…These cases come in addition to the reported early-onset epileptic encephalopathy related to mutations in aaRS genes[25][26][27][28] and confirm the high epileptogenic potential of these mutations. These cases come in addition to the reported early-onset epileptic encephalopathy related to mutations in aaRS genes[25][26][27][28] and confirm the high epileptogenic potential of these mutations.…”
supporting
confidence: 74%
“…These cases come in addition to the reported early-onset epileptic encephalopathy related to mutations in aaRS genes[25][26][27][28] and confirm the high epileptogenic potential of these mutations. These cases come in addition to the reported early-onset epileptic encephalopathy related to mutations in aaRS genes[25][26][27][28] and confirm the high epileptogenic potential of these mutations.…”
supporting
confidence: 74%
“…Aminoacylation of mt-tRNA-Cys was analysed as described previously 22. Briefly, total RNA was extracted from fibroblasts using Trizol reagent (Life Technologies) following the manufacturer's instructions, with the final pellet resuspended in 10 mM NaOAc at pH 5.0 and kept at 4°C to preserve the aminoacylation state.…”
Section: Methodsmentioning
confidence: 99%
“…For example, mutations in mitochondrial ARS enzymes that cause recessive diseases can directly affect protein solubility [74] or impair mitochondrial protein translation [4,5,46,50,5659,63,7579], consistent with a loss-of-function effect. With respect to ARS mutations that cause dominant peripheral neuropathy, structural analyses have revealed that the majority of GARS mutations affect residues within the dimer interface [80].…”
Section: Models To Study the Mechanism Of Ars Mutations In Human Diseasementioning
confidence: 99%